Real-time welding defect classification using peak count analysis of current signals with statistical validation - Afidatusshimah, Mazlan; Hamdan, Daniyal; Mohd Herwan, Sulaiman; Mahadzir, Ishak@Muhammad (Institute of Physics, 2025)
Welding is a critical process in heavy industries such as construction, automotive, and oil and gas, where weld quality directly impacts structural performance and safety. Traditional non-destructive testing (NDT) methods, although effective, are often labour-intensive, costly, and reliant on operator expertise. This study investigates an alternative approach using real-time monitoring of welding current signals to identify defects based on peak count variations. Under controlled laboratory conditions, welding current signals were captured and segmented into 1 mm intervals for detailed analysis. Statistical evaluation using Analysis of Variance (ANOVA) and Tukey’s post-hoc tests in R Studio revealed significant differences in peak distributions across various defect types. Good welds consistently exhibited 8-17 peaks per segment, while defects such as Lack of Penetration (LOP), Lack of Fusion (LOF), Burn-through, and Excess Weld displayed distinctive peak count deviations. These results confirm that peak count analysis is a statistically significant and reliable metric for real-time weld quality assessment. The findings lay the foundation for future development of intelligent welding systems capable of automated defect detection and adaptive process control.